ANALISIS DESAIN SISTEM BIAYA STANDAR: STUDI KASUS PT KW - Michael Widyanata; Vikko Agarian; Titin Pranoto; Yang Elvi Adelina (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
This study analyzes the calculation of product costs in companies included in the category of MSMEs (Micro, Small and Medium Enterprises) in Indonesia, which is a sand mining companies. This study uses a Cost System Design framework that  consist of four aspects, namely quality data, external financial reporting, calculation of product costs, and controls and implementation of strategies that will affect the company’s Cost System Design Stage. This study also uses standard cost and variance to analyze cost control. This qualitative research gathering data by using the triangulation method. The result is the company was in the first phase of the Four Stage Cost System Design. Based on the results, there are differences in production costs that are favorable. In addition, the results of this study also found deficiencies in the company's internal control system. In this study, there are limitations in the form of incomplete data obtained and some data are estimates from management. Research contributes to the results in the form of a calculation framework and design of a cost system for companies that is useful for calculating the cost of goods sold and inventory values that have not been calculated before.